(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Motor skills are learned sequences of movements that are combined to produce a smooth, efficient action in order to master a particular task. Arm strength and flexibility are basic essential need for all sports and games. Sports training are the basic form of an athlete’s training. It is the preparation systematically organized with the help of exercises, which in fact is a pedagogically organized process of controlling an athlete’s development. Purpose: The purpose of the study was to quantification of motor ability components in response to high intensity interval training and moderate-intensity continuous training among college women athletes. Method: Forty five (N=45) women athletes were selected as subjects. They were divided randomly into three groups of fifteen each i.e., (n=15) Group-I underwent high-intensity interval training (HIIT), Group-II underwent moderate-intensity continuous training (MICT) and Group-III acted as control group (CG). The training period was limited to three days per week for twelve weeks. Among the motor ability components arm strength and flexibility were selected as dependent variables. Arm strength was measured through push ups test and flexibility was assessed through sit & reach test. All the subjects were tested prior to and immediately after the experimental period on the selected dependent variable. The data obtained from the experimental groups and control group before and after the experimental period were statistically analyzed with Analysis of covariance (ANCOVA). Whenever the ‘F’ ratio for adjusted post test means was found to be significant, the Scheffe’s Post hoc test was applied to determine the paired mean differences. The level of confidence was fixed at 0.05 level for all the cases. Results: High-intensity interval training (HIIT) was found to be better than the Moderate-intensity continuous training (MICT) and Control group in developing arm strength and flexibility.